Molecular Association Studies on Polyvinyl Alcohol at Different Concentrations - Richa Saxena; S. C. Bhatt (Advances in Materials Science and Engineering)
Ultrasonic velocities, densities, and viscosities have been measured for the solution of polyvinyl alcohol in water at concentration range of 0.3% to 1% at temperature 35°C. Ultrasonic velocities have been measured using variable path ultrasonic interferometer at 1 MHz frequency. The acoustical parameters like adiabatic compressibility, acoustic impedance, intermolecular free length, and relaxation time have been calculated by using above-mentioned values of ultrasonic velocities, densities, and viscosities. The variation of these acoustical parameters is explained in terms of solute-solvent interaction in a polymer solution.